NUTRITIONAL RECOMMENDATIONS DURING LONG-TERM ADMINISTRATION OF GLUCOCORTICOIDS - Požar, Hajnalka F (Medicinski časopis, 2023)
Glucocorticoids are highly effective medications used for the treatment of inflammatory and autoimmune disorders in rheumatology, pulmonology and neurology. However, using these medications for a long period of time, or in excessive doses, carries the risk of unwanted effects. Most of the typical side effects can be successfully prevented or reduced with adequate nutritional strategies. Increased appetite and weight gain can be reduced with regular meals with a selection of fresh, unprocessed foods in accordance with the principles of proper nutrition. Hypertension requires a reduced salt intake by < 3.75 g (1/2 teaspoon), along with the use of other herbs spices. Insulin resistance and elevated blood sugar levels can be possible reduced, avoiding foods rich simple carbohydrates, sugar and preferring complex carbohydrates (whole grains, starchy foods, fruits, vegetables). Due to the high risk of osteoporosis, it is recommended to consume three servings of dairy products and fish per day in order to obtain an adequate intake of vitamin D. However, patients may find these recommendations unclear or overly strict, and they may require assistance, motivation, and repetition of information for practical application these advice in everyday life.